2018
DOI: 10.1590/0034-7167-2017-0953
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anxiety disorders as a cause of workers’ absence

Abstract: Objective: to analyze the prevalence of various anxiety disorders among mental and behavioral disorders as a cause for the leave of absence of workers in the state of Piauí. Method: transversal census-based study performed with data from the National Social Security Institute. Four-hundred twelve leaves of absence of workers due to anxiety disorders in the 2015-2016 biennium were included. Results: higher prevalence was found for mixed anxiety-depressed disorder (31.2%), followed by other anxious disorders (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
13

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 19 publications
2
9
0
13
Order By: Relevance
“…Transtornos de ansiedade, por sua vez, são derivados da junção de um sentimento de ansiedade exacerbado e medo vago, somado a desordens de comportamento. Portanto, os transtornos diferem da ansiedade por serem mais excessivos a ponto de atrapalharem ações cotidianas e por perdurarem por um longo tempo (Fernandes et al, 2018).…”
Section: Resultsunclassified
“…Transtornos de ansiedade, por sua vez, são derivados da junção de um sentimento de ansiedade exacerbado e medo vago, somado a desordens de comportamento. Portanto, os transtornos diferem da ansiedade por serem mais excessivos a ponto de atrapalharem ações cotidianas e por perdurarem por um longo tempo (Fernandes et al, 2018).…”
Section: Resultsunclassified
“…Quesitos como a escolaridade e a situação conjugal ainda causam discordância na literatura sobre a influência no surgimento da depressão (Fernandes et al, 2018). Todavia, estudos tem mostrado que pessoas sem companheiro fixo apresentam maior risco de depressão, comparadas com aquelas que vivem com o companheiro (Stopa et al, 2015).…”
Section: Discussionunclassified
“…A depressão é considerada a principal responsável por incapacidades funcionais e conduz a piores condições de saúde geral entre populações de diferentes países (Lannes, 2018). A doença é responsável por parte considerável de afastamentos laborais, acarretando desemprego e perca da estabilidade, na população adulta jovem esse fato se agrava quando ocorre o transtorno misto ansioso e depressivo (Neto, Feitosa, Sidrim, Morais & Oliveira, 2020;Fernandes et al, 2018). Essa incapacidade de trabalho reforça-se em fatores psicossociais como a alta exigência para o trabalho, baixo apoio social, Research, Society and Development, v. 10, n. 4, e45110414246, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i4.14246 desequilíbrio esforço-recompensa e comprometimento excessivo, recorrendo-se aos auxílios previdenciários, submetendo-se aos protocolos da perícia para comprovar inaptidão temporária ou definitiva (Silva-júnior & Fischer, 2015;Silva, Terra, & Crippa, 2017).…”
Section: Discussionunclassified
“…Besides, the association between CMD and non-use of the helmet might indicate patients with mental disorders usually fail to perform self-care (Martins et al, 2016). Also, in more severe cases, to adopt self-destructive behaviours that put their lives and others at risk, since such disorders interfere with the individual's functional capacity in different aspects of daily living (Fernandes et al, 2018). Our findings add to the literature, for example, research by Mollanorouzi, Mirabbasi, Rouhani & Hasanpour (2014) on anxiety (one symptom of CMD) in motorcyclists and associated factors identified that all participants (n = 73) had mild anxiety; 21%, moderate anxiety and 6%, severe anxiety.…”
Section: Discussionmentioning
confidence: 99%